Risk Factors Causing Preterm Labor - Evren Kurtul Çam; Nejat Demircan; Ülkü Özmen Bayar; Füruzan Köktürk; İlker İnan Arıkan (Medical Network, 2016)
OBJECTIVE: The aim of this study was to determine the risk factors, that may cause preterm labor among the pregnant women. STUDY DESIGN: Our study was performed between the dates 1st September 2008 - 1st May 2009, among pregnant women, who are hospitalized in Obstetrics and Gynecology Department of Bülent Ecevit University Faculty of Medicine. A survey sheet was constituted to determine possible risk factors of preterm labor. RESULTS: Variables, which were evaluated as significant according to Logistic Regression Analysis, were found as age, systolic blood pressure, multiple pregnancies, presence of chronic disease, anemia, intercourse, experiencing a bitter event within the last month, trauma, low income and leukocytosis. CONCLUSIONS: Conditions related to low socio-cultural level, high blood pressure, stress, multiple pregnancies, therapeutic pregnancies, vaginal infections, presence of a chronic disease, or severe anemia led us to suspect about preterm labor; risk factors should be eliminated by intensive monitoring of these pregnant women.